Sustainability of family properties in the southeastern Pernambuco - an application of the MESMIS method (Research, Society and Development, 2021)
The search for actions to mitigate environmental degradation caused by the current conventional agricultural model has encouraged the use of indicators, which help decision-making and contribute to the sustainability of agroecosystems. Thus, the aim of this study was to assess the sustainability of family properties. The research took place in ten properties in Pernambuco's municipalities: Bom Conselho, Garanhuns, Jucati and Saloá. The MESMIS method was chosen, which resulted in the following results: the characterization of the agroecosystems drew a general panorama and the relationship between farmers and agroecosystems; the analysis of critical points pointed out factors that interfere with sustainability such as labor, technical assistance, soil and water; the construction of indicators took into account the opinion of farmers, critical points, literature study, attributes and the three central dimensions of sustainability (environmental, economic and social). After applying the indicators, all agroecosystems achieved an overall average of regular sustainability, requiring improvement in aspects such as soil quality, lack of water, technical assistance and agroecological management. The method used is presented as a self-management tool capable of evaluating the current situation of an agroecosystem, as well as subsidizing techniques aimed at sustainability.